2019
DOI: 10.3390/polym11040692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution Composition Variables on Electrospun Alginate Nanofibers: Response Surface Analysis

Abstract: Alginate is a promising biocompatible and biodegradable polymer for production of nanofibers for drug delivery and tissue engineering. However, alginate is difficult to electrospin due to its polyelectrolyte nature. The aim was to improve the ‘electrospinability’ of alginate with addition of exceptionally high molecular weight poly(ethylene oxide) (PEO) as a co-polymer. The compositions of the polymer-blend solutions for electrospinning were varied for PEO molecular weight, total (alginate plus PEO) polymer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
1
42
0
1
Order By: Relevance
“…Currently, electrospinning is the most popular method to produce nanofibers with uniform diameter distribution [23,24,25,26]. However, electrospinning still has some serious disadvantages, such as low spinning rate (less than 1 mL/h) and high energy consumption [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, electrospinning is the most popular method to produce nanofibers with uniform diameter distribution [23,24,25,26]. However, electrospinning still has some serious disadvantages, such as low spinning rate (less than 1 mL/h) and high energy consumption [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber formation, diameter, and morphology depend on both solution properties, like concentration, density, conductivity, and surface tension, as well as experimental parameters, including solution flow rate, tip-tocollector distance, and applied voltage. [32][33][34][35][36][37][38][39][40] The high surface area to volume ratios and high porosities of these nanofiber mats make them suitable for many biomedical applications, including protective clothing, 41 wound dressing, 32,42 vascular grafts, 43 and drug delivery. 31 Previously, it has been demonstrated that electrospinning can be used to encapsulate a wide variety of viable bacteria, including Gram-negative and Grampositive cells into dry nanofiber mats.…”
Section: Introductionmentioning
confidence: 99%
“…Plasticity contributes to nanofiber formation, and elasticity is critical in the stage of jet formation and elongation, preventing the jet from breaking up. A higher G ′ results consequently in a beadless nanofiber structure [ 39 ]. In this case, both co-polymer solutions show a higher storage modulus than the loss one, it being greater for PCLGA.…”
Section: Resultsmentioning
confidence: 99%